Case on “To buy, or not to Buy” - T., Senthil Kumar (Penerbit UMP, 2017)
Joy is a fresh graduate employed at a local bank. As a commerce graduate he was quite interested in the financial markets of the country. He came from a middle income family and had set big dreams on his professional and personal life. He was certain that it would be difficult to achieve greater heights by solely depending on the salary. So, he had picked up the habit of closely observing the stock prices of potential companies and invested in those stocks if the financials were good.